Studying Social Media Burnout and Problematic Social Media use: The implication of perfectionism and metacognitions - Nina Harren (Elsevier, 2021)
Social Media Burnout (SMB) is a relatively new Internet-related issue, and has garnered interest in research this past decade. Prior studies found significant associations between perfectionism and metacognitions with anxiety, stress-related disorders, and Internet-related disorders. This present study explored connections between problematic social media use (PSM), perfectionism, metacognitions, online cognitions, and SMB to identify factors that might contribute to SMB. A sample of 825 participants, aged from 18 to 75 years old (M ​= ​30, SD ​= ​11.9), with 700 (85%) female participants, completed an online survey measuring problematic Instagram use (PIgU), problematic Facebook use (PFU), perfectionism, metacognitions, online cognitions, and SMB. Overall, Pearson's Correlations indicated that both PIgU and PFU were each associated to four out of five metacognition dimensions, and were associated to dimensions of perfectionism. A Multiple linear regression analysis indicated that SMB was significantly impacted by age, PIgU, all online cognition subscales, socially prescribed positive perfectionism, self-oriented negative perfectionism, and metacognitive beliefs about uncontrollability of thoughts and danger. Considering that SMB is a new topic, findings of this study provide new information about factors that are potentially implicated in SMB (PSM, perfectionism, metacognitions, online cognitions). Implications for further research were discussed.